AN ANALYTICAL LITERATURE REVIEW EXAMINING THE DEVELOPMENT OF E-COMMERCE IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
In today's technology-driven world, advancements in all forms of business have paved the way for electronic transactions on a global scale, shrinking the world into a global village. E-commerce, which refers to buying and selling goods or services, or transferring funds or data over the internet, has emerged as a significant player in the market. It encompasses various types of transactions, such as business-to-business, business-to-consumer, consumer-to-consumer, or consumer-to-business. E-commerce has brought numerous benefits to society, including cost-effectiveness, increased efficiency, customization, vast options, and time-saving. Consumers can easily purchase goods from the comfort of their homes or offices with just a click of a mouse button. Furthermore, online services such as banking, e-ticketing, bill payments, and hotel bookings have been tremendously beneficial for customers. However, this study aims to analyze the evolution, growth, benefits, drawbacks, and challenges of e-commerce. This review highlights the critical role that e-commerce plays in India's economy and provides valuable insights into the opportunities and challenges facing the industry. The findings of this review have important implications for policymakers, practitioners, and researchers interested in understanding the development of e-commerce in India and its potential impact on the broader economy. Further research is needed to explore in-depth the implications of e-commerce for the Indian economy and to provide insights into how the sector can be leveraged for inclusive economic growth.